2020
DOI: 10.1016/j.ejor.2020.04.013
|View full text |Cite
|
Sign up to set email alerts
|

A preference learning framework for multiple criteria sorting with diverse additive value models and valued assignment examples

Abstract: We present a preference learning framework for multiple criteria sorting. We consider sorting procedures applying an additive value model with diverse types of marginal value functions (including linear, piecewise-linear, splined, and general monotone ones) under a unified analytical framework. Differently from the existing sorting methods that infer a preference model from crisp decision examples, where each reference alternative is assigned to a unique class, our framework allows to consider valued assignmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(5 citation statements)
references
References 40 publications
0
3
0
2
Order By: Relevance
“…This is reinforced by Liu, et al (2020) that additional tasks in learning can be a preference for improving student learning outcomes. This is because students are trained to optimize each other's skills in a flexible, effective, and consistent interaction pattern [34]. In line with this, Zhang, et al (2022) also reported that meaningful learning combined in discovery learning-based assignments can associate understanding in building information through assignment instructions completed in groups.…”
Section: Resultsmentioning
confidence: 93%
“…This is reinforced by Liu, et al (2020) that additional tasks in learning can be a preference for improving student learning outcomes. This is because students are trained to optimize each other's skills in a flexible, effective, and consistent interaction pattern [34]. In line with this, Zhang, et al (2022) also reported that meaningful learning combined in discovery learning-based assignments can associate understanding in building information through assignment instructions completed in groups.…”
Section: Resultsmentioning
confidence: 93%
“…A gestão de dados deve estar alinhada com a organização das operações, sendo responsabilidade dos gestores florestais coordenarem esses esforços. Após a obtenção dos dados, os gestores florestais são capazes de extrair informações úteis e tomar decisões mais bem informadas como, por exemplo, estimar a produtividade florestal, sob diferentes configurações de trabalho (KUDYBA, 2018;LIU et al, 2020;SHI et al, 2022).…”
Section: Introductionunclassified
“…Forest managers, through datasets, are able to extract useful information and make better-informed decisions that include, for example, estimating the productivity of timber harvesters. Development of a model to predict dynamic productivity behavior of machines, under different configurations, can contribute to optimization of the operation [28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%